Pengaruh Kebijakan Utang, Good Corporate Governance, Cash Holding, Dan Sales Growth Terhadap Nilai Perusahaan (Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2021) - Selli Agustianingrum; Titiek Suwarti; Gregorius N. Masdjojo (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effects of debt policy, good corporate governance, cash holding, and sales growth on the value of the company. The method used in this research is a quantitative method through secondary data in the form of financial information of manufacturing companies listed on the Indonesia Stock Exchange starting in 2018 until 2021. Data obtained from www.idx.co.id and www.finance.yahoo.com, and the company's official website. The sampling technique used was purposive sampling and this study used a sample of 188 observations. In conducting data testing using analytical methods, namely multiple linear analysis of panel data using eviews 12 software. The results showed that good corporate governance debt policy, and cash holding had no effect on firm value, while sales growth had a positive effect on firm value. Keywords: Debt Policy, Good Corporate Governance, Cash Holding, Firm Value, Sales Growth